PAJAK DAN ASPEK HUKUM PERDATA - Hulman Panjaitan (to-ra, 2018)
Taxes can be studied or analyzed from various disciplines, including law. Tax talks from the point of view of law are called tax laws. Civil law aspects, are a big part of tax law. Tax is an engagement. Many institutions con- tained in binding law as regulated in book III of the Civil Code are used in tax law. Keyword : taxes; tax laws; regulatation tax.